PEMANFAATAN MANGGA ARUM MANIS DALAM PEMBUATAN DODOL DENGAN PERBEDAAN KONSENTRASI TEPUNG KETAN DAN RUMPUT LAUT - Pasaribu, Hamid Ucok; Ali, Akhyar; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Utilization of cotton candy mango in directly encourage mango processing into derived products. One cotton candy mango derivative products is Dodol. Dodol is expected to be high in fiber. Fiber can be obtained from the addition of seaweed in the manufacture Dodol. The purpose of research is the use in the manufacture of cotton candy mango Dodol with different concentrations ofb glutinous rice and seaweed. The study was conducted using a completely randomized design (CRD) with 4 treatments and 4 replications. Each study uses comparative glutinous rice and seaweed that is different in each treatment including K1R1 (85:15), K2R2 (80:20), K3R3 (75:25) and K4R4 (70: 30). Parameters measured were moisture content, ash, crude fiber, and organoleptic. The best treatmentis K1R1with sticky riceflour ratio of 85% and15% moisture content of grass yield 10.14; ash content of 0.39; crude fiber of 8.30 overall acceptance. Keywords: Arum manis mango, seaweed, glutinous rice, dodol